KARAKTERISTIK MORFOLOGI Ganoderma steyaertanum YANG MENYERANG KEBUN BENIH Acacia mangium DAN Acacia auriculiformis DI WONOGIRI, JAWA TENGAH - Nur Hidayati; Siti Husna Nurrohmah (Jurnal Pemuliaan Tanaman Hutan, 2015)
Acacia mangium and Acacia auriculiformis seed orchards on the island of Java are associated with a different species of Ganoderma. The importance of G. steyaertanum as a pathogen of forest trees has not been previously highlighted. The aim of this study is to look at the characteristics of the G. steyaertanum which attacks two Acacia seed orchads at Wonogiri Central Java. Activities undertaken are to identify the signs of the G. steyaertanum both in the field and in the laboratory. Characterization of fungi is conventionally done by observing the morphology of signs, such as the shape and color of the fruit body, shape and color of mycelium. Morphological characteristic applied in this study has proved to be effective to identify the pathogen. G. steyaertanum was isolated from fruitbodies of affected trees and pathogenicity tests confirmed Koch’s postulates. Somatic incompatibility tests demonstrated high genetic variability of the pathogen.